Elucidating the bioremediation mechanism of Scenedesmus sp. IITRIND2 under cadmium stress. (November 2021) - Tripathi, Shweta; Arora, Neha; Pruthi, Vikas; Poluri, Krishna Mohan
Abstract: Cadmium (Cd) is a non-biodegradable pollutant that has become a global threat due to its bioaccumulation and biomagnification in higher trophic levels of the food chain. Green technologies such as phycoremediation is an emerging approach and possess edge over conventional methods to remediate Cd from the environment. The present investigation elucidates the adaptive mechanism of a freshwater microalga, Scenedesmus sp. IITRIND2 under Cd stress. The microalga showed excellent tolerance to Cd stress with IC50 value of ~32 ppm. The microalga showed phenomenal removal efficiency (~80%) when exposed to 25 ppm of Cd. Such a high uptake of Cd by the cells was accompanied with increased total lipid content (~33% of dry cell weight). Additionally, the elevated level of ROS, lipid peroxidation, glycine-betaine, and antioxidant enzymes evidenced the activation of efficient antioxidant machinery for alleviating the Cd stress. Further, analysis of the fatty acid methyl ester (FAME) presented a steady increase in saturated and polyunsaturated fatty acids with biodiesel properties complying the American and European fuel standards. The study proposes an integrated approach for bioremediation of toxic Cd using hyper-tolerant microalgal strains along with biodiesel production from the generated algal biomass. Graphical abstract: Image 1 Highlights: Scenedesmus sp. IITRIND2 exhibited high IC50 value of 31.7 ppm under Cd stress. The microalga successfully bio-remediated ~80–90% Cd from media. Rise in APX, GR, and CAT activities assisted Cd tolerance in cells. Scenedesmus sp. IITRIND2 augmented ~33% lipid content under Cd stress.